Microbial and physicochemical changes during fermentation of Thai chicken sausage - Vanichpun, Apinya (2003)
A newly formulated fermented Thai chicken sausage was developed by mixing chicken meat with glutinous rice, sugar, garlic, salt, and black pepper. Glutinous rice rendered good binding of the mixed ingredients when compared to other carbohydrate sources (rice, glass noodle, rice + glass noodle, and glutinous rice + glass noodle). Moreover, glutinous rice also significantly (p<0.05) reduced the pH value from 6.06 to 4.42 when compared to the formulation with added rice (from 5.80 to 4.50), rice + glass noodle (from 5.77 to 4.43), and glutinous rice + glass noodle (from 5.82 to 4.34) within 24h of fermentation. The addition of water (5% w/w) with and without sodium tripolyphosphate (0.2% w/w) significantly (p<0.05) improved moisture retention in the sausages. Sodium tripolyphosphate (STPP) and water significantly (p<0.05) affect the pH reduction and the growth of lactic acid bacteria. The formation of mainly lactic acid from 4.96 to 23 mmol of acid/ 100g of samples and a small amount of acetic acid from 1.57 to 3.27 mmol of acid/ 100 / of samples as a result of carbohydrate fermentation by LAB during Oh-48h fermentation contributed to the acidic aroma and typical tangy taste typically found in Thai fermented sausages. The fermentation process was successfully carried out within 48h as shown by the rapid increase in the growth of LAB from 7.80 log10cfu/g t012.46 log10cfu/g, rapid increase in titratable acidity from 0.90 to 2.25 g of lactic acid/ 100 g of sausages, and sharp decrease in pH values from 5.64 to 4.27. Prolonged fermentation (after 48h) caused an over acidity in the sausages with a final pH between 4.20-4.30. This newly formulated fermented chicken sausage proved to be highly selective for the growth of LAB. Four species of LAB namely, Pediococcus pentosaceus, Pd. acidilactici, Lactobacillus pentosus, and Lb. brevis were isolated. Pd. pentosaceus and Pd. acidilactici were found throughout the fermentation process, whereas Lb. pentosus and Lb. brevis were found after 24h of fermentation, indicating that the latter two species are tolerant to the acidic conditions. Pd. pentosaceus was found throughout the fermentation process in higher number than other species.